2016
DOI: 10.1681/asn.2016020232
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Evaluation of Total Glomerular Number and Capillary Tuft Size in Nephritic Kidneys Using Lightsheet Microscopy

Abstract: The total number of glomeruli is a fundamental parameter of kidney function but very difficult to determine using standard methodology. Here, we counted all individual glomeruli in murine kidneys and sized the capillary tufts by combining in vivo fluorescence labeling of endothelial cells, a novel tissue-clearing technique, lightsheet microscopy, and automated registration by image analysis. Total hands-on time per organ was <1 hour, and automated counting/sizing was finished in <3 hours. We also investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
291
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(323 citation statements)
references
References 33 publications
13
291
0
Order By: Relevance
“…The MF-HREM analysis revealed a glomeruli distribution that was consistent with their known spatial distribution and with other measures for wild-type (WT) adult mice performed with light sheet or in vivo MRI (39,43) MF-HREM pixel size was 2.17 μm lateral and 2.58 μm axial, enabling identify glomeruli which had a minimum volume of 24×10 5 μm 3 .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The MF-HREM analysis revealed a glomeruli distribution that was consistent with their known spatial distribution and with other measures for wild-type (WT) adult mice performed with light sheet or in vivo MRI (39,43) MF-HREM pixel size was 2.17 μm lateral and 2.58 μm axial, enabling identify glomeruli which had a minimum volume of 24×10 5 μm 3 .…”
Section: Resultssupporting
confidence: 73%
“…The final step is the outcome of the connected components analysis and hence quantification of glomeruli number, and volume distribution. These data show the expected distribution and size of glomeruli for heathy WT mouse as compared with other techniques(39), (43).…”
Section: Resultssupporting
confidence: 60%
“…However, mammalian tissues are naturally opaque, hindering high-resolution imaging in any tissue deeper than a few hundred micrometers-a major reason why sectioning is needed for histological examination of target organs 1 . Recent innovations in tissue clearing technology now allow 3D histological examination of intact organs [2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Tissue clearing is a chemical process aiming to match refractive indices throughout intact tissues, thus rendering them transparent and allowing deep tissue fluorescent microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…3a and Supplementary Videos 3 and 4 ). We found that ECi-clearing ( n = 1.56) is well-suited for this application due to its clearing efficacy, as well as low toxicity [19]. A custom HIVEX holder ( n = 1.55) was machined with channels to accommodate multiple biopsies (13 in this case) and to keep them aligned and parallel.…”
Section: Main Textmentioning
confidence: 99%